Quantifying generalized trust in individuals and counties using language - Giorgi, Salvatore; Jones, Jason Jeffrey; Buffone, Anneke; Eichstaedt, Johannes C.; Crutchley, Patrick; Yaden, David B.; Elstein, Jeanette; Zamani, Mohammadzaman; Kregor, Jennifer; Smith, Laura; Seligman, Martin E. P.; Kern, Margaret L.; et al. (Frontiers in Social Psychology, 2024)
Trust is predictive of civic cooperation and economic growth. Recently, the U.S. public has demonstrated increased partisan division and a surveyed decline in trust in institutions. There is a need to quantify individual and community levels of trust unobtrusively and at scale. Using observations of language across more than 16,000 Facebook users, along with their self-reported generalized trust score, we develop and evaluate a language-based assessment of generalized trust. We then apply the assessment to more than 1.6 billion geotagged tweets collected between 2009 and 2015 and derive estimates of trust across 2,041 U.S. counties. We find generalized trust was associated with more affiliative words (love, we, and friends) and less angry words (hate and stupid) but only had a weak association with social words primarily driven by strong negative associations with general othering terms (“they” and “people”). At the county level, associations with the Centers for Disease Control and Prevention (CDC) and Gallup surveys suggest that people in high-trust counties were physically healthier and more satisfied with their community and their lives. Our study demonstrates that generalized trust levels can be estimated from language as a low-cost, unobtrusive method to monitor variations in trust in large populations.